The Influence 0f Game-based Learning Strategies and Game-based Learning on Mathematics Learning - Ayesha, Belia; Ernesto, Abdulkarim (International Journal of Educational Technology and Artificial Intelligence, 2023)
This study aimed to compare the effect of game-based learning strategies and metaverse-based learning on mathematics learning. There are two learning strategies: game-based learning strategies as the control class and metaverse-based learning strategies as the experimental class. Learning independence is divided into high-learning-independence groups and low-learning-independence groups. This study used a quasi-experimental method with an Anova treatment design by level 2x2. The results showed that: (1) there was no significant difference in the learning outcomes of students who were taught using game-based learning strategies compared to metaverse-based learning g strategies. The research findings indicated that Game-based mathematics learning strategies can be implemented to support digital learning without an internet connection. At the same time, metaverse-based mathematics learning can be implemented to support learning using an internet connection.